SUN-188 Intra-Articular Triamcinolone Injections - a “Slipped” Cause of Cushing’s Syndrome - Shi, Melody (J Endocr Soc, 2020)
Background: Triamcinolone injections are used to treat various orthopedic and rheumatologic conditions; their effects on the hypothalamic pituitary adrenal axis have not been well characterized. Clinical Case: A 14 yo female was referred to our clinic for evaluation of low TSH (0.16 µIU/mL) and possible hyperthyroidism. There was no goiter and she appeared euthyroid and had normal free T4 (1.01 ng/dl) but she had typical features of Cushing syndrome (CS), including round facies, thinning of hair, fatigue, truncal adiposity, violaceous striae, facial hirsutism and oligomenorrhea. She was previously healthy and participated in many sports. She did not report any history of exogenous glucocorticoid use but the fasting ACTH (4 pg/ml) and cortisol (0.1 µg/dl) levels were suppressed. Subsequent chart review revealed that she received intra-articular Triamcinolone (TA) to treat “slipping rib” syndrome. This included 3 injections of Kenalog 40 mg/mL, the last in July 2019. Her cumulative TA dose was 440 mg, the equivalent of prednisone 550 mg. Triamcinolone acetonide 1.4 mcg/dL (normal 0-0.1, analyzed by LC-MS/MS) was detected in the urine over 3 months after her last injection. Conclusion: - Levels of ACTH and cortisol can be suppressed for several months after intra-articular corticosteroid injections, placing the patient at subsequent risk for adrenal crisis - In some cases, high doses of Triamcinolone administered by intra-articular injection can cause clinical Cushing syndrome